Juvenile dermatomyositis and nephrotic syndrome: A case report and a mini literature review - Zhou, Weiran; Dong, Linlin; Liu, Xuemei; Dong, Chunhua; Zhang, Hongxia (Frontiers in Pediatrics, 2023)
Abstract Background Renal involvement is rarely reported in juvenile dermatomyositis and may be caused by the toxic effects of myoglobinuria or an autoimmune reaction.We report a case of dermatomyositis and nephrotic syndrome in a child to explore the association between juvenile dermatomyositis and renal involvement. Case presentation An 8-year-old girl with skin rash, edema, proximal muscle weakness predominantly involving the lower extremities, low-grade fever, and foamy urine was admitted to our hospital. Her laboratory tests met the criteria of nephrotic syndrome. She had elevated creatine kinase and lactate dehydrogenase and was diagnosed with juvenile dermatomyositis after electromyography and muscle MRI. Anti-NXP2 antibodies were positive. Her proteinuria was relieved soon after treatment with prednisone and methotrexate, but her muscle strength progressively decreased. The disease was relieved after pulse methylprednisolone treatment and mycophenolate mofetil, but recurred after drug reduction with mild proteinuria. Adalimumab was used for treatment and helped reduce the doses of glucocorticoid and mycophenolate mofetil. Conclusions Juvenile dermatomyositis may be one of the rare causes of nephrotic syndrome. The mechanism involved in JDM combined with renal injury may be multifactorial. Autoantibodies may play important roles in both muscle and renal damage.